Computational study of nitro-benzylidene phenazine as dengue virus-2 NS2B-NS3 protease inhibitor - Salin, Nurul Hanim; Hariono, Maywan; Khalili, Nur Sarah Dyana; Zakaria, Iffah Izzati; Saqallah, Fadi G.; Mohamad Taib, Mohamad Nurul Azmi; Kamarulzaman, Ezatul Ezleen; Wahab, Habibah A.; Khawory, Muhammad Hidhir (Frontiers in Molecular Biosciences, 2022)
According to WHO, and as of week 23 of 2022, more than 1,311 dengue cases with 13 deaths were reported in Malaysia. Furthermore, there has been an increase of 65.7% during the same period in 2021. Despite the increase in the cumulative dengue incidence, there is no effective antiviral drug available for dengue treatment. The aim of this work is to evaluate several nitro-benzylidene phenazine compounds,especiallythosethat contain 4-hydroxy-3,5-bis((2-(4-nitrophenyl)hydrazinylidene)-methyl)benzoate through pharmacophore queries selection method as potential dengue virus 2 (DENV2) NS2B-NS3 protease inhibitors. Herein, molecular docking was employed to correlate selected hits’ free binding energies and their binding affinities. Besides, Pan assay interference compounds (PAINS) filter was adopted to identify and assess the drug-likeness, toxicity, mutagenicity potentials, and pharmacokinetic profiles to select hit compounds that can be considered as lead DENV2 NS2B-NS3 protease inhibitors. Molecular dynamics assessment of two nitro-benzylidene phenazine derivatives bearing dinitro and hydroxy groups at the benzylidene ring showed their stability at the main binding pocket of DENV2 protease, where their MM-PBSA binding energies were between -22.53 and -17.01 kcal/mol. This work reports those two nitro-benzylidene phenazine derivatives as hits with 52-55% efficiency as antiviral candidates. Therefore, further optimisation is required to minimise the lead compounds’ toxicity and mutagenicity.